Low Socioeconomic Status Is Associated with Reduced Access to Natriuretic Peptide Testing in the Outpatient Setting: A Population-based Evaluation - Ismail R. Raslan, MD, MSc; Anna Chu, MHSc; Peter C. Austin, PhD; Xuesong Wang, MSc; David Bobrowski, MD; Barbara S. Doumouras, MD; Joseph J. Lee, BSc; Candace D. McNaughton, MD, PhD; Peter A. Kavsak, PhD; Husam Abdel-Qadir, MD, PhD; Heather J. Ross, MD, MHSc; Douglas S. Lee, MD, PhD (CJC Open)
Background: Tests of natriuretic peptide (NP) concentrations are guideline-recommended for diagnosis and prognostication in heart failure (HF). Although NP testing is available at some hospitals, outpatient access has been limited to those who can pay out-of-pocket. We investigated whether residents who have lower socioeconomic status have differential access to NP testing. Methods: Using a case-control design, we compared patients who had NP tests with age-matched patients undergoing non-NP blood tests (January 2015-June 2020), performed in the outpatient or acute hospital setting. The association of socioeconomic status measures (eg, deprivation quintile) with receipt of NP testing was assessed using conditional logistic regression, adjusted for sex, test location, and comorbidities, and was stratified by incidence of prior HF. Results: Among 96,919 patients without prior HF (median age, 72 years; 50% female) who underwent NP testing, the majority of tests (66.6%) were performed in an acute hospital setting rather than in an outpatient clinic. Residents of more-deprived neighbourhoods had a higher incidence of HF (P < 0.001), but they were more likely to undergo NP testing in an acute care setting (odds ratio [OR] for most- vs least-deprived, 1.269; 95% confidence interval [CI], 1.104-1.216) and less likely to undergo testing as outpatients (OR, 0.807; 95% CI, 0.764-0.853 vs least-deprived; all P < 0.001). Among 70,362 matched patients with known HF (median aged, 78 years; 45% female), outpatient NP testing was also less likely to be performed among patients living in the most-deprived neighbourhoods (OR, 0.723; 95% CI, 0.677-0.772; P < 0.001). Conclusions: Although those of lower socioeconomic status exhibit a higher risk of incident HF, they had less NP testing performed in outpatient settings, and more testing performed in resource-intense acute-care settings. Résumé: Contexte: Le dosage des peptides natriurétiques (PN) est recommandé par les lignes directrices pour le diagnostic et le pronostic de l’insuffisance cardiaque (IC). Bien que le dosage des PN puisse être réalisé dans certains hôpitaux, en ce qui concerne les cliniques de consultation externe, il n’est accessible que pour les patients qui peuvent le payer de leur poche. Nous avons cherché à savoir si l’accès au dosage des PN était différent pour les personnes d’un statut socioéconomique inférieur. Méthodologie: À l’aide d’une méthode cas-témoin, nous avons comparé des patients qui avaient eu un dosage des PN avec des patients du même âge qui avaient eu des analyses sanguines sans dosage des PN (janvier 2015 — juin 2020) dans des cliniques de consultation externe et des hôpitaux de soins de courte durée. Le lien entre les mesures du statut socioéconomique (p. ex., quintile de défavorisation) et la réception d’un dosage des PN a été évalué au moyen d’une régression logistique conditionnelle, ajustée pour le sexe, le lieu du dosage et les maladies concomitantes et a été stratifié selon la présence d’antécédents d’IC. Résultats: Chez 96 919 patients sans antécédents d’IC (âge médian : 72 ans; 50 % de femmes) ayant eu un dosage des PN, la majorité (66,6 %) des dosages ont été réalisés dans un hôpital de soins de courte durée plutôt que dans une clinique de consultation externe. Les résidents des quartiers plus défavorisés affichaient une plus grande fréquence d’IC (p < 0,001), mais ils étaient plus susceptibles de passer un dosage des PN dans un hôpital de soins de courte durée (rapport des cotes [RC] pour les plus défavorisés par rapport aux moins défavorisés, 1,269; intervalle de confiance [IC] à 95 % : 1,104-1,216) et moins susceptibles de passer un dosage en consultation externe (RC, 0,807; IC à 95 % : 0,764-0,853 par rapport aux résidents moins défavorisés; p < 0,001 pour tous). Parmi 70 362 patients appariés atteints d’IC connue (âge médian, 78 ans; 45 % de femmes), le dosage des PN dans les cliniques de consultation externe était également moins susceptible d’être réalisé chez des patients provenant de quartiers plus défavorisés (RC, 0,723; IC à 95 % : 0,677-0,772; p < 0,001). Conclusions: Bien que les personnes d’un statut socioéconomique inférieur présentent un risque accru d’IC incidente, elles ont été moins nombreuses à recevoir un dosage des PN en consultation externe, et les dosages ont davantage été effectués dans des établissements de soins de courte durée ayant beaucoup de ressources.